Komunikasi Kelompok Pickers dalam Membentuk Kelompok Kustom Kultur - Frisardi Ramadhana; Wiki Angga Wiksana (UNISBA Press, 2024)
Abstract. Kustom kultur is a creation of American society aimed at describing a work of art, vehicles, and fashions of the people who built and drove cars or motorcycles in America in the 1950s. Pickers is a business in the fashion industry or often called a brand that is involved in the cultural custom scene. Whether intentional or naturally formed, Pickers that started a Brand, has its own group. The purpose of this study is (1) knowing what factors make Pickers can develop in the world of Kustom kultur (2) knowing the communication patterns applied by the owner of the Pickers so that they can form a group (3) knowing the barriers to communication patterns experienced by the Pickers. Data collection was conducted through interviews with Chandra as the owner who became the key informant, as well as several members of his group to corroborate the results of the study. The focus of the problem raised in this study is how the communication patterns that the owner of the Pickers apply to the Custom group Culture. Observation and documentation is also a way to collect data so that this research is optimal. Pickers can be known to many culture custom lovers making the curiosity of researchers the main cornerstone. Not only in terms of fashion that Chandra sells at his Pickers Store, some of the events that Chandra makes and the activities of his group in the field of Kustom kultur become interesting things to be researched. Abstrak. Kustom Kultur adalah sebuah ciptaan masyarakat Amerika bertujuan untuk menggambarkan sebuah karya seni, kendaraan, dan mode orang-orang yang membangun dan mengendarai mobil atau motor di Amerika pada tahun 1950. Pickers adalah sebuah bisnis di industri fesyen atau sering disebut brand yang berkecimpung di skena Kustom Kultur. Entah disengaja atau terbentuk secara alami, Pickers yang bermula sebuah Brand, memiliki kelompoknya sendiri. Tujuan pada penelitian ini yaitu (1) mengetahui faktor apa yang membuat Pickers dapat berkembang di dunia Kustom Kultur (2) mengetahui pola komunikasi yang diterapkan pemilik Pickers sehingga mampu membentuk kelompoknya (3) mengetahui hambatan pola komunikasi yang di alami oleh Pickers. Pengumpulan data dilakukan melalu wawancara dengan Chandra selaku pemilik yang menjadi key Informan , juga beberapa anggota kelompoknya untuk menguatkan hasil penelitian. Fokus masalah yang di angkat pada penelitian ini adalah bagaimana pola komunikasi yang pemilik Pickers terapkan kepada kelompok Kustom Kulturnya. Observasi dan dokumentasi juga menjadi cara mengumpulkan data agar penelitian ini optimal. Pickers bisa dikenal banyak pecinta Kustom Kultur menjadikan rasa ingin tahu peneliti menjadi landasan utamanya. Tidak hanya dari sisi fesyen yang Chandra jual di Pickers Store nya, beberapa event yang Chandra buat dan ke aktifan kelompoknya di bidang Kustom Kultur menjadi hal yang menarik untuk di teliti.